Bovine delta papillomavirus E5 oncoprotein negatively regulates the cGAS-STING signaling pathway in cattle in a spontaneous model of viral disease - De Falco, Francesca; Cutarelli, Anna; Catoi, Adriana Florinela; Uberti, Barbara Degli; Cuccaro, Bianca; Roperto, Sante (Frontiers in Immunology, 2022)
Abstract. Persistent infection and tumorigenesis by papillomaviruses (PVs) require viral manipulation of various cellular processes, including those involved in innate immune responses. The cyclic guanosine monophosphate-adenosine monophosphate synthase-stimulator of interferon genes (cGAS-STING) pathway has emerged as an essential innate immune sensing system, that recognizes DNA and trigger potent antiviral effector responses. In this study, we found that bovine PV (BPV) E5 protein, the major oncoprotein of bovine delta PVs, interacts with STING but not with cGAS in a spontaneous BPV infection of neoplastic urothelial cells of cattle. Real-time RT-PCR revealed a significant reduction in both cGAS and STING transcripts in E5-expressing cells. Furthermore, western blot (WB) analysis failed to detect any variation in the expression of interferon-inducible protein 16 (IFI16), an upstream effector of the STING pathway. A ternary complex composed of E5/STING/IFI16 was also observed. Co-immunoprecipitation studies showed that STING interacts with a protein network composed of total and phosphorylated TANK-binding kinase 1 (TBK1), total and phosphorylated interferon regulatory factor 3 (IRF3), IRF7, IKKα, IKKβ, IKKε, ELKS, MEKK3, and TAK1. RT-qPCR revealed a significant reduction in TBK1 mRNA levels in BPV-infected cells. WB analysis revealed significantly reduced expression levels of pTBK1, which is essential for the activation and phosphorylation of IRF3, a prerequisite for the latter to enter the nucleus to activate type 1 IFN genes. WB also revealed significantly down-expression of IKKα, IKKβ, IKKε, and overexpression of IRF7, ELKS, MEKK3, and TAK1in BPV-positive urothelial cells compared with that in uninfected healthy cells. Phosphorylated p65 (p-p65) was significantly reduced in both the nuclear and cytosolic compartments of BPV-infected cells compared with that in uninfected urothelial cells. Our results suggest that the innate immune signaling pathway mediated by cGAS-STING is impaired in cells infected with BPV. Therefore, effective immune responses are not elicited against these viruses, which facilitates persistent viral infection and subsequent tumorigenesis.